Reports of Cubiceps baxteri McCulloch 1923 from Indian Ocean are probably misidentifications of Cubiceps whiteleggii (Waite 1894) - Viji, V.; Harish, K.c.; Kurup, B. Madhusoodana (Zootaxa, 2021)
Cubiceps baxteri McCulloch 1923 was described based on a single, imperfect (devoid of a tail) stranded specimen collected from a beach in Lord Howe Island, Tasman Sea. Though C. baxteri was reported as a widely distributed tropical species (Butler 1979), it was mainly a result of its incorrect identification (see Agafonova 1994; Stewart and Last 2015). The distribution of C. baxteri is reported to be restricted to the Pacific Ocean, from Japan and eastwards to Baja California (Mexico), southwards to the Hawaiian Islands, New South Wales (Australia), and Lord Howe Island (Tasman Sea) to the Southern parts of Chile (Eschmeyer et al. 2017; Mundy 2005; Agafonova 1994).